The effects of typical ageing on cognitive control: recent advances and future directions - Dexter, Melissa; Ossmy, Ori (Frontiers in Aging Neuroscience, 2023)
Cognitive control is a multifaceted construct relating to the regulation of thoughts and behaviours, including the multiple mechanisms that help to manage and process sensory information during goaldirected tasks, such as planning and decision making. These are essential functions that allows us to navigate through life and its many challenges. Understanding the aging of cognitive control mechanisms provides insights into how age-related changes impact daily functioning and help inform interventions to maintain cognitive health and well-being in older adults. Nevertheless, the ageing research has often taken a narrow focus. This article reviews the dominant research from the past two decades and explores gaps for future study, with the hope of encouraging innovative research into age-related declines in cognitive control. We first introduce the traditional perspectives in the field, then we explore more contemporary approaches while highlighting the plasticity and compensatory mechanisms in the ageing brain. We end with suggestions for future directions including the need to consider ageing as a cascadic effect informed by multiple processes and factors that drive change throughout an individual's lifetime.